2016
DOI: 10.3389/fmicb.2015.01494
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Viral Abundance and Diversity in a Sphagnum-Dominated Peatland: Temporal Fluctuations Prevail Over Habitat

Abstract: Viruses impact microbial activity and carbon cycling in various environments, but their diversity and ecological importance in Sphagnum-peatlands are unknown. Abundances of viral particles and prokaryotes were monitored bi-monthly at a fen and a bog at two different layers of the peat surface. Viral particle abundance ranged from 1.7 x 106 to 5.6 x 108 particles mL-1, and did not differ between fen and bog but showed seasonal fluctuations. These fluctuations were positively correlated with prokaryote abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 100 publications
1
14
0
Order By: Relevance
“…Description of bacteriophage populations in Sphagnum peatlands is currently limited to the ssDNA viruses of the Microviridae (45) and Caudovirales (46) observed in metagenomics data, although it appears that phages are the most abundant biological entities in the Sphagnum phyllosphere (46). Given this, and the dominance of bacteria in the Sphagnum microbiome as previously described (15), the relatively low abundance of active bacteriophage in our samples was a surprise.…”
Section: Discussionmentioning
confidence: 59%
“…Description of bacteriophage populations in Sphagnum peatlands is currently limited to the ssDNA viruses of the Microviridae (45) and Caudovirales (46) observed in metagenomics data, although it appears that phages are the most abundant biological entities in the Sphagnum phyllosphere (46). Given this, and the dominance of bacteria in the Sphagnum microbiome as previously described (15), the relatively low abundance of active bacteriophage in our samples was a surprise.…”
Section: Discussionmentioning
confidence: 59%
“…3 ), and this finding is consistent with results in aquatic systems and sediments ( Brum, Schenck & Sullivan, 2013 ). Soil virus literature to date, suggests viral community structure is not different with depth (based on genetic material; Adriaenssens & Cowan, 2014 ), nor does abundance change (comparing 5–10 cm and 10–15 cm from soil pore water; Ballaud et al, 2015 ), but viral abundance was reported to vary seasonally ( Ballaud et al, 2015 ). To this end, we tested storing both shallow and deep soil samples at chilled (4 °C) and frozen temperatures (−80 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Metagenomic studies in rainforest soils indicate that viral species richness is greater than bacterial species richness by an order of magnitude where moisture content and OM are high ( Fierer et al, 2007 ; reviewed in Kimura et al, 2008 ). Additionally, viral diversity may be greater in soils than in marine water column environments, because soil microorganisms are thought to be more diverse than marine microorganisms ( Torsvik, Øvreås & Thingstad, 2002 ; Weinbauer & Rassoulzadegan, 2004 ; Smalla & Van Elsas, 2010 ; Tamames et al, 2010 ; Crump, Amaral-Zettler & Kling, 2012 ), and viral and microbial diversity are correlated ( Maranger & Bird, 1995 ; Anesio et al, 2004 ; Ballaud et al, 2015 ). In addition, soil viruses have clear seasonal population dynamics with different temporal and spatial distributions ( Ashelford et al, 1999 ; Ashelford et al, 2000 ; Ballaud et al, 2015 ), which could act as mechanisms for maintaining the coexistence of a diverse community ( Chesson, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, virus-focused metagenomics studies either concentrate virus-genomes via their virions or enrich for double-stranded RNA that is a broadly shared feature of virus replication. The virus-enriched nucleic acids are then sequenced by shotgun metagenomics methods (Bibby 2013) for the detection of viruses in environmental material, including marine water (Schmidt et al 2014), fresh water (Mohiuddin & Schellhorn 2015), soil (Ballaud et al 2016), crop plants (Aw et al 2016), native plants and weed plant species (Blouin et al 2016). We remain unable to recommend a single molecular approach to comprehensively target all of the diversity of viral material for metabarcoding studies in an unbiased manner, i.e.…”
Section: Recommendationmentioning
confidence: 99%